Echoes from the caves: Qumran and the New Testament - García Martínez, Florentino (Studies on the texts of the desert of Judah, 2009)
The 16 contributions of experts both in the study of the Dead Sea Scrolls and on the study of the New Testament analyze the relationship among the two corpora. Some of the studies propose a general understanding of the relationship, other apply it to concrete topics or texts